(untitled) (Research, Society and Development, 2020)
Luminescent semiconductor nanocrystals or quantum dots (QDs) emerge as important fluorescent probes for in vitro and in vivo Trypanosoma cruzi cells studies. However, to ensure applicability to living organisms, several tests still need to be done. Since several toxic events are caused by QDs, such as loss of mitochondrial membrane potential, ROS generation, DNA damage and cell death by autophagy. We performed a review of the literature on mechanisms of cellular uptake, internalization and citotoxicity of nanoparticles including our results about the evaluation of biological toxicity in T. cruzi. We evaluated the possible effects on parasite growth curves in a time - scale of control and incubated cells with different concentrations of CdTe – QDs (0.2; 2.0; 20 and 200µM) to determine the development cells changes. In addition, intracellular ROS were measured by Electron Paramagnetic Resonance Spectroscopy (EPR) technique. According our results, we can infer that the toxic effects of QDs in T. cruzi are dose-dependent and that high levels of ROS are involved in cellular toxicity promoted by higher concentrations of QDs. In summary, parasites labeled with low concentrations of nanoparticles are suitable and can be used as bioimaging tools for living parasites. However, more studies on QDs cytotoxicity need to be carried out.